Analysis of Household Debt in South Africa Pre- and Post-Low-Quality Asset Financial Crisis - Kereeditse, Michelle Koketso; Mpundu, Mubanga (International Journal of Economics and Financial Issues, 2021)
Many economies including South Africa experience high levels of debt. This paper analyses household indebtedness in South Africa from 2005Q1, a period where there was a massive escalation of asset prices, stock prices had gone up and house prices more than doubled to 2019Q4. This timeframe was chosen to identify the level of household debt prior to the 2007-2009 financial crisis, during, as well as after the recession and just before the COVID-19 pandemic spread globally from China. The variables used in the study comprised of the dependent which was household debt and independent variables were consumption, income, consumer price index, taxation and inflation. The VECM model and various diagnostic tests where employed to explain the variables. The Generalized Impulse Response Function (GIRF) were also utilized to look at the dynamic relations among the variables under investigation. There was a positive insignificant relationship between household debt and consumption, a negative insignificant relationship between the dependent variable and income, a positive significant relationship amongst household debt and consumer price index. From the findings, it was concluded that household debt in South Africa has in fact changed over the past 14 years with middle income households having to overcome the burden of their expenditure. Keywords: Household Debt, Saving, Economic growth, Financial Crisis, Borrowing JEL Classifications: F10, F40, I18 DOI: https://doi.org/10.32479/ijefi.11476